2020
DOI: 10.1080/02701367.2019.1679333
|View full text |Cite
|
Sign up to set email alerts
|

Functional Resistance Training Superiority Over Conventional Training in Metabolic Syndrome: A Randomized Clinical Trial

Abstract: Metabolic syndrome (MetS) is a growing epidemic related with higher values of blood pressure (BP) and autonomic dysfunction. Scientific evidence has been indicating that functional resistance training (FRT) is superior over conventional (CRT) for muscle fatigue and pain, yet its effects on autonomic modulation (AM), BP and heart rate in MetS are unclear.We theorized that FRT can be superior to CRT in MetS patients because of larger muscle activation. This study compares FRT and CRT on AM, blood pressure, heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Traditional Chinese medicine has the characteristics of many active ingredients, mild effects, and small side effects. As an antifatigue drug, the research and development of traditional Chinese medicine has broad prospects [ 7 ]. Acanthopanax senticosus is the dry root and rhizome or stem of Acanthopanax senticosus, a plant belonging to Acanthopanax senticosus family.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine has the characteristics of many active ingredients, mild effects, and small side effects. As an antifatigue drug, the research and development of traditional Chinese medicine has broad prospects [ 7 ]. Acanthopanax senticosus is the dry root and rhizome or stem of Acanthopanax senticosus, a plant belonging to Acanthopanax senticosus family.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a snowball search was conducted in the 8 RCTs that met the inclusion criteria, and 2 more eligible studies were identified and included for final analysis. Therefore, 10 RCTs [16][17][18][19][20][21][22][23][24][25] were included in this systematic review and meta-analysis. The study selection process is shown in Figure 1.…”
Section: Studies Included In the Systematic Reviewmentioning
confidence: 99%
“…The study selection process is shown in Figure 1. As shown in Table 1, the included RCTs were conducted in different countries (Australia, Brazil, Denmark, England, Italy, Lithuania, New Zealand, Republic of South Korea, and Saudi Arabia), and all 10 reported HRV parameters in patients with overweight and obesity, 16,18,25 type 2 diabetes mellitus, 17,19,20,22,24 and metabolic syndrome 21,23 as primary outcomes. In total, there were 398 participants, 205 were assigned to the HIIT, MICT, or DST intervention group and 193 to the control group.…”
Section: Studies Included In the Systematic Reviewmentioning
confidence: 99%
“…Functional resistance training has been a part of the training program in some treatment methods for chronic heart and liver diseases. These exercises were previously used for therapeutic effects on metabolic syndrome and have had positive results in indicators of, Obesity, hyperglycemia, high blood pressure, and hypertriglyceridemia 13 . Also, the studies showed that functional resistance training increased parasympathetic excitability in the autonomic function of the heart and was reported as an anti-fibrillation effect in improving ventricular function 14 .…”
Section: Introductionmentioning
confidence: 99%